Co-vulnerabilities of inhibiting carbonic anhydrase IX in ferroptosis-mediated tumor cell death - McDonald, Paul C.; Dedhar, Shoukat (Frontiers in Molecular Biosciences, 2023)
The tumour-associated carbonic anhydrases (CA) IX and XII are upregulated by cancer cells to combat cellular and metabolic stress imparted by hypoxia and acidosis in solid tumours. Owing to its tumour-specific expression and function, CAIX is an attractive therapeutic target and this has driven intense efforts to develop pharmacologic agents to target its activity, including small molecule inhibitors. Many studies in multiple solid tumour models have demonstrated that targeting CAIX activity with the selective CAIX/XII inhibitor, SLC-0111, results in anti-tumour efficacy, particularly when used in combination with chemotherapy or immune checkpoint blockade, and has now advanced to the clinic. However, it has been observed that sustainability and durability of CAIX inhibition, even in combination with chemotherapy agents, is limited by the occurrence of adaptive resistance, resulting in tumour recurrence. Importantly, the data from these models demonstrates that CAIX inhibition may sensitize tumour cells to cytotoxic drugs and evidence now points to ferroptosis, an iron-dependent form of regulated cell death (RCD) that results from accumulation of toxic levels of phospholipid peroxidation as a major mechanism involved in CAIX-mediated sensitization to cancer therapy. In this mini-review, we discuss recent advances demonstrating the mechanistic role CAIX plays in sensitizing cancer cells to ferroptosis.